Problem, objectives and data analysis: A methodological reflection in psychological research - Ramos-Galarza, Carlos (2019)
In this article, the existing relationship between the elements that compose the structure of a research: question, hypotheses, objectives and statistical analyses are analyzed. Emphasis is placed on the interrelation that each of these elements must possess, which become the foundation of each phase that is being built in an investigation. When talking about the research question, mention is made of the scientific question that arises after having identified a gap in a line of research. The next element into consideration are the hypotheses, this article deep into the hypotheses of descriptive type, correlation, comparison of groups, causality and intervention. When comes to talk about the research objectives, there will be mentioned thedegree of complexity of each verb that must be used according to the statistical analyses that will be conducted. The work is closed considering the need for an investigation which must be configured as a machinery, where each gear must allow the study executed have a harmonious presentation.